Analisis Metode Antrean Single Phase – Multi Channel dalam Pelayanan pada Uniqlo Trans Studio Bandung (TSB) - Andra Hafidz Fadhilah; Ayi Tejaningrum (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the cashier queueing system at Uniqlo Trans Studio Bandung using the Single Phase–Multi Channel (M/M/s) queueing model. The study focuses on the implementation of the existing queueing system, the analysis of queue performance based on the Single Phase–Multi Channel method, and the comparison of queue performance before and after the analysis to determine the efficiency of cashier services. This study employs a quantitative method with a descriptive approach. Data were collected through direct observation, interviews, and documentation of cashier service activities at Uniqlo Trans Studio Bandung. The collected data include customer arrival rates, service times, the number of operating cashiers, queue lengths, and customer waiting times. The data were then analyzed using the Single Phase–Multi Channel (M/M/s) queueing model to calculate the service utilization rate, the average number of customers in the queue, the average number of customers in the system, the average waiting time in the queue, and the average time spent by customers in the system. The expected results of this study are to provide an overview of the cashier queueing system at Uniqlo Trans Studio Bandung, determine the efficiency level of the service based on the Single Phase–Multi Channel method, and provide recommendations regarding the optimal number of cashiers and queue management. Therefore, the findings are expected to serve as a reference for management in improving operational efficiency and service quality, thereby enhancing customer satisfaction.